Products From Olive Tree 2016
DOI: 10.5772/64988
|View full text |Cite
|
Sign up to set email alerts
|

Modern Techniques in the Production of Table Olives

Abstract: The olive tree (Olea europaea L.) is one of the most important trees in the world, and olive oil and table olives are consumed extensively as a basic ingredient of the Mediterranean diet. Table olives are prepared from the fruit of a variety of cultivated olive trees, and, after removing their bitterness by several methods, they are preserved by natural fermentation or other methods before packing. Currently, scientists and consumers alike are interested in and prefer fresh and healthy table olives that have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 117 publications
(231 reference statements)
0
11
0
Order By: Relevance
“…A high consumption of sodium (>2 g/d, equivalent to 5 g salt/d) and low consumption of potassium (<3•5 g/d) contribute to high BP and increase risk of CVD and stroke (152) . It is suggested that a diet rich in potassium and calcium and poor in sodium prevents the development of osteoporosis and/or colon cancer, in addition to their effects on CV health (153,154) . Strategies at individual and governmental levels may be adopted to reduce the intake of NaCl.…”
Section: Salt Reduction In Table Olives: a Potential Innovationmentioning
confidence: 99%
“…A high consumption of sodium (>2 g/d, equivalent to 5 g salt/d) and low consumption of potassium (<3•5 g/d) contribute to high BP and increase risk of CVD and stroke (152) . It is suggested that a diet rich in potassium and calcium and poor in sodium prevents the development of osteoporosis and/or colon cancer, in addition to their effects on CV health (153,154) . Strategies at individual and governmental levels may be adopted to reduce the intake of NaCl.…”
Section: Salt Reduction In Table Olives: a Potential Innovationmentioning
confidence: 99%
“…In industrial applications, chlorinated water (50–200 ppm as free chlorine, 1–2 min, and pH = 6.0–7.5) are used extensively to wash fruits and vegetables. Studies have shown that chlorine dips can reduce the population of microorganisms below 2 log colony forming unit (cfu), but it has the potential to react with organic materials to form harmful by-products, therefore it should not be used in high doses (Degirmencioglu, 2016 ).…”
Section: Pre-processing Of Olivesmentioning
confidence: 99%
“…The latter exhibit higher residual levels in food due to their non-solubility in water (Ikeura et al, 2011 ; Iizuka and Shimizu, 2014 ), and most of pesticides residues are retained on fruit and vegetable surface, and may be also absorbed into the flesh (Bajwa and Sandhu, 2014 ). The various food processing methods such as washing (added with strong oxidizing agents, such as ozone, chlorine dioxide), peeling, brushing, blanching, cooking, boiling, etc., can be used to reduce pesticide contamination (González-Rodríguez et al, 2011 ; Bajwa and Sandhu, 2014 ; Misra, 2015 ; Degirmencioglu, 2016 ; Qi et al, 2018 ).…”
Section: Pre-processing Of Olivesmentioning
confidence: 99%
See 2 more Smart Citations